RETRACTED: Assessment of the Risk of Hemochromatosis in Polytransfused Sickle Cell Patients at the Abidjan Transfusion Therapy Unit - Mamadou Sekongo Yassongui; Saydou Kabore; Boidy Kouakou; Sidonie Kouamenan; Kadidja Kassogue; Parfait N’Guessan; Nabo Bertin Oue; Seidou Konate; Ibrahima Sanogo (Journal of Hematalogy and Oncology Research, 2020)
This article has been retracted on 29 January 2021. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2372-6601.jhor-25-5854) In Côte d'Ivoire, sickle cell disease affects 14% of the population. It is responsible for significant morbidity and mortality. Transfusion is a significant element in the management of major sickle cell anemia, which exposes them to post-transfusion hemochromatosis. The biological diagnosis is based on the determination of serum iron and the transferrin saturation coefficient (CST). As the determination of the CST was not available in our exercise context in Côte d'Ivoire, we determined only the ferritinemia. The interest of this work lies in the therapeutic implication linked to the identification of patients at risk of hemochromatosis because chelators are difficult to access for most patients. This was a prospective, descriptive and analytical study, on polytransfused sickle cell patients, followed at the transfusion therapy unit (UTT) of the CNTS of Abidjan, from 2010 to 2018. We included 78 sickle cell patients, all ages and genders who have received at least ten transfusions. The ferritinemia assay was carried out by ELISA. Transfusion exchange, with 59% of cases, was the most used mode of transfusion. The mean ferritinemia was 1719.19 ng / ml. Hyperferritinemia was found in 63% of patients. Most of the patients were on a long-term transfusion program with an average of 27.5 bags of red blood cell concentrates. Thirty-two patients had received at least 20 bags of red blood cell concentrates. We noted 21 patients treated, including 3 with deferoxamine and 18 treated with oral deferasirox. We have identified 33 sickle cell anemia patients at risk for hemochromatosis. The determinants of the risk of hemochromatosis were the high number of blood bags and the method of transfusion.
Keywords: hemochromatosis